DEVELOPMENT OF THE PUBLIC SERVICE MANAGEMENT INFORMATION SYSTEM THROUGH EXTREME PROGRAMMING IN SUKARAME DISTRICT, BANDAR LAMPUNG - Widiastuti, Ika; Cakranegara, Pandu Adi (International Journal of Multidisciplinary Research and Literature, 2022)
There are still obstacles to providing public services such as administrative services and population data in Sukarame District. To store data, they still use Microsoft Office so that people cannot access it. Therefore, a system is needed to improve public services. This research aims to identify and discuss general management information systems by applying extreme programming at the Sukarame District office, Bandar Lampung. The research method is qualitative. The study results are that to improve performance. An information system is needed by applying extreme programming that aims to make it easier to make electricity application permits, business licenses, public complaint systems, and online sub-district profiles